The Power of Survey Design : A User's Guide for Managing Surveys, Interpreting Results, and Influencing Respondents - Iarossi, Giuseppe (Washington, DC: World Bank, 2012)
The vast majority of data used for economic research, analysis, and policy design comes from surveys-surveys of households, firms, schools, hospitals, and market participants, and, the accuracy of the estimate will depend on how well the survey is done. This innovative book is both a 'how-to' go about carrying out high-quality surveys, especially in the challenging environment of developing countries, and a 'user's guide' for anyone who uses statistical data. Reading this book will provide data users with a wealth of insight into what kinds of problems, or biases to look for in different data sources, based on the underlying survey approaches that were used to generate the data. In that sense the book is an invaluable 'skeptics guide to data'. Yet, the broad storyline of the book is something that should be absorbed by statistical data users. The book will teach and show how difficult it often is to obtain reliable estimates of important social and economic facts, and, therefore encourages you to approach all estimates with sensible caution.